MANAJEMEN KEARSIPAN DALAM MEWUJUDKAN TATA KELOLA ADMINISTRASI DI CV AGRO TRI SANTOSA - Puspasari, Durinda; Widodo, Cahyo (Prodi Pendidikan Ekonomi Universitas Mulawarman, 2023)
This research aims to find out about archives management in realizing administrative governance at CV Agro Tri Santosa, obstacles in archives management to realize administrative governance, and archives management efforts in realizing administrative governance at CV Agro Tri Santosa. This research uses descriptive research with a qualitative approach method. The data taken in the research is primary data obtained through direct interviews from managers and secretaries from CV Agro Tri Santosa, while secondary data can be obtained through interviews and documentation with employees. The subjects of this research are 3 employees who manage archives and the object of this research is archive management in realizing administrative governance.The technique for selecting subjects for this research is by using a purposive sampling technique. The data collection technique in this research is by interviews and documentation. The research results show that archives management in administrative management has been carried out well, but there are still obstacles in realizing administrative governance. This obstacle is the handling of archives which is not in accordance with the handling of archives management. There are efforts in archival management, namely by handling, maintaining, storing, processing and recording properly so that they suit the needs of CV Agro Tri Santosa.